Groups associated with modules over nearrings - Artemovych, O.D.; Kravets, I.V. (Algebra and Discrete Mathematics, 2007)
We construct a group D(I, T) associated with the pair (I, T), where I is a nontrivial distributive submodule of a left N-module G, T is a nontrivial subgroup of the unit group U(N) of a right nearring N with an identity element, and find criteria for D(I, T) to be a Frobenius group. We construct a group D(I, T) associated with the pair (I, T), where I is a nontrivial distributive submodule of a left N-module G, T is a nontrivial subgroup of the unit group U(N) of a right nearring N with an identity element, and find criteria for D(I, T) to be a Frobenius group.